2018
DOI: 10.1016/j.jnn.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of neonatal pressure injuries

Abstract: Pressure injuries in the neonatal unit can cause infection, unnecessary pain and have the potential for scarring. However there is a dearth of information available on this topic.Preventative strategies to address pressure injury development are essential when caring for vulnerable neonatal patients. This article highlights the issues regarding neonatal pressure injuries in clinical practice. In addition, it explores skin assessment and discusses the use of a neonatal skin risk assessment tool as a quality imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 21 publications
0
20
0
6
Order By: Relevance
“…19 It has also been discussed by previous researchers that it is not enough to just score an infant; a skin risk assessment tool needs to provide a skin care and documentation plan to standardised current practice in a NICU. 14,18,19 Many risk assessment tools just provide staff caring for the neonate with a score which informs them that the neonate may or may not be at risk of a skin injury with no instructions on the timing and type of care required to reduce the risk of skin injuries. The SRAMT Health Services Insights acknowledges all neonates are at risk and identifies levels of risk (low, mod, high extreme).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…19 It has also been discussed by previous researchers that it is not enough to just score an infant; a skin risk assessment tool needs to provide a skin care and documentation plan to standardised current practice in a NICU. 14,18,19 Many risk assessment tools just provide staff caring for the neonate with a score which informs them that the neonate may or may not be at risk of a skin injury with no instructions on the timing and type of care required to reduce the risk of skin injuries. The SRAMT Health Services Insights acknowledges all neonates are at risk and identifies levels of risk (low, mod, high extreme).…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge the previous research that has recommended such a tool should be used as part of routine clinical assessment. 1,18,19 In this project, we were keen to see whether the SRAMT would predict as accurately as members of nursing team who had experience in managing neonates across gestation and acuity levels. This study had shown the SRAMT was more accurate than the experienced staff.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations